What is the role and importance of temperature measuring devices in finger replantation surgery? Thermal measurement devices for replantation - Ahmedov , Anvar; Aksoy, Alper (Journal of Surgery and Medicine, 2022)
Background/Aim: Post-operative circulation monitoring is very important in replantation surgery. Vascular pathologies that occur can be detected and undergo intervention as a result of strict follow-up protocols, thus increasing success rates. Although many alternative methods for circulation monitoring are available, no gold standard for such monitoring exists. This study aimed to find a more reliable and easier method by comparing different temperature measurement methods to facilitate the follow-up of patients who underwent finger replantation after the operation. Methods: This study was designed as a retrospective case series study. It was conducted between January 2017 and December 2019. Eighteen patients who presented with flexor zone 2 finger amputations and who had undergone replantation surgery were included in the study. The cases were randomly divided into two equal groups. While the finger temperature of the patients in the first group was measured with an indoor/outdoor temperature device, the measurement was obtained using a non-contact infrared thermometer in the second group. Results: In our study, the mean age of group 1 was 44.33 years, and the mean age of group 2 was 45. Eleven fingers from nine patients in the group 1 and 10 fingers in 9 patients in the group 2 were replanted. All amputated finger replantation were performed. The patients stayed in the hospital for five days, were followed, and treated. The success rate based on living fingers was 54.54% in group 1 and 60% in group 2. The mean measured finger temperatures were 34.12 and 35.76 °C in groups 1 and 2, respectively. In group 1, the mean time of measurement was calculated as 4 min 31 s. In the group 2, the mean time of measurement was calculated as 1 s. In the study, two measurement tools were used to determine fingertip temperatures in the two similar groups. Conclusion: In our study, we found that infrared non-contact temperature measuring devices are both reliable and useful as a heat meter in the follow-up of finger after the replantation operation.